Penyelesaian Tindak Pidana Penipuan Melalui Pendekatan Restorative Justice Di Kepolisian Resor Purworejo - Ratna Sary Gayatri; Sulistyanta Sulistyanta (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The aim of this research is to determine the implementation of restorative justice in resolving criminal acts of fraud at the Purworejo Police Station and to determine the obstacles experienced by investigators at the Purworejo Police Station in resolving criminal acts of fraud using a restorative justice approach. This research uses empirical legal research with a legal sociology approach. The crime of fraud is a crime against property. Losses incurred as a result of criminal acts of fraud are in the form of material, whether in the form of money or property. When the loss has been returned, punishment is no longer necessary. The process of resolving criminal acts of fraud through restorative justice at the Purworejo Police Station has been going well and is in accordance with the Republic of Indonesia State Police Regulation No. 8 of 2021. In resolving criminal acts of fraud through restorative justice at the Purworejo Resort Police, there are 2 obstacles, namely obstacles in terms of regulations and obstacles in terms of implementation